Are UK immigrants selected on education, skills, health and social networks? - Renee Luthra; Lucinda Platt (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
It is assumed that not only will more highly educated migrants do better in the receiving country labour market, but also that those who are relatively more educated compared to their compatriots, that is who are 'selected', will bring additional forms of human and social capital associated with economic success. Given the lack of information on these traits in most datasets, this assumption has not yet been comprehensively tested. Combining information on usually unobserved labour market relevant skills and characteristics with measures of educational selection and labour market outcomes of the foreign born in the UK, we do not find that educational selection is systematically associated with better cognitive or non-cognitive skills, health or social network composition. For more elite migration streams, educational selectivity is negatively associated with skills. As a result, higher selection does not translate into better labour market outcomes net of education. We argue that while higher bars to migration may increase the absolute skill level of migrants, it may also exclude those with (usually unobserved) favourable labour market characteristics who lack social and financial capital, reinforcing transnational class reproduction rather than selecting for the brightest and the best.
Keywords: 330; selectivity; immigration; migrant heterogeneity; labour market; employment wages; gender